2022
DOI: 10.1177/15330338221109650
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Recurrence of Glioblastoma Versus Grade 4 IDH-Mutant Astrocytoma Following Chemoradiation: A Retrospective Matched-Cohort Analysis

Abstract: Background and Purpose: To quantitatively compare the recurrence patterns of glioblastoma (isocitrate dehydrogenase-wild type) versus grade 4 isocitrate dehydrogenase-mutant astrocytoma (wild type isocitrate dehydrogenase and mutant isocitrate dehydrogenase, respectively) following primary chemoradiation. Materials and Methods: A retrospective matched cohort of 22 wild type isocitrate dehydrogenase and 22 mutant isocitrate dehydrogenase patients were matched by sex, extent of resection, and corpus callosum inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…In our case, the patient first was treated toxoplasmosis, based of the biopsy, however condition of the patient was worsening rapidly progressive the presentation of cystic lesion massively growing which is indicated to operate immediately, under subtotal accessible resection with biopsy and second pathological analysis which was last result was glioblastoma grade IV, in our case immediate referred to the radiotherapy and chemotherapy, but the patient developed cutaneous collection of the pus, which is made impossible to start his radio and chemotherapy [7].…”
Section: Discussionmentioning
confidence: 65%
“…In our case, the patient first was treated toxoplasmosis, based of the biopsy, however condition of the patient was worsening rapidly progressive the presentation of cystic lesion massively growing which is indicated to operate immediately, under subtotal accessible resection with biopsy and second pathological analysis which was last result was glioblastoma grade IV, in our case immediate referred to the radiotherapy and chemotherapy, but the patient developed cutaneous collection of the pus, which is made impossible to start his radio and chemotherapy [7].…”
Section: Discussionmentioning
confidence: 65%
“…Recent literature showed that IDH‐mutant astrocytoma and IDH‐wildtype glioblastoma had different recurrence patterns following chemoradiation; therefore in vivo identification of IDH mutation among grade 4 glioma could be of great interest in the future [14]. Our work including 39 histologically confirmed recurrent HGGs showed that IDH‐mutant gliomas (astrocytoma grade 4 and oligodendroglioma grade 3) had higher 18F‐FDOPA uptake (TBRmax) than IDH‐wildtype HGGs.…”
Section: Discussionmentioning
confidence: 71%
“…A multi-center study shown that patients with primary IDH-mutant glioblastoma can have an overall survival bene t from TMZ and concurrent radiochemotherapy [12]. Followed the progression of WHO 4 glioblastoma/astrocytoma, the recurrent IDH-mutant astrocytoma was less likely to extend beyond gross tumor volume and indicated a modi ed plan of radiotherapy or radiochemotherapy [13].…”
Section: Discussionmentioning
confidence: 99%